Concept of Penentuan Sebelum Pembagian (PSP) in the Distribution of Inheritance from Islamic Inheritance Perspective: Konsep Penentuan Sebelum Distribusi (PSP) dalam Distribusi Warisan dari Perspektif Warisan Islam - Kanggas, Fazari Zul Hasmi; Akmal, Haerul; Muthoharoh, Intan; Marjany, Nawa (Transformatif, 2026)
The distribution of inheritance or inherited property is an issue that is always interesting to discuss in the academic world. Of course, there are many factors behind this, including the distribution of inheritance that is not in line with fiqh mawaris, or the use of terms that are often used as jargon in the distribution of inheritance, such as "Determination before Distribution (PSP). This study aims to understand the concept of PSP, which requires individuals to refer to the Qur'an and hadith to determine the shares of the heirs in a literal manner. In contrast, inheritance distribution is based on the heirs' willingness. Thus, to address these concerns, this study uses a qualitative legal research method with a doctrinal and conceptual approach. The research data consists of primary and secondary legal materials, including verses from the Qur'an, hadiths on inheritance, classical fiqh literature, and official CMS documents and guidelines related to the implementation of PSP. This study does not involve participants directly because it is normative-doctrinal in nature. Data collection techniques involved library research, including systematic searches of Islamic legal sources and relevant documents. Data analysis was carried out qualitatively through normative interpretation and conceptual-comparative analysis between classical inheritance fiqh provisions and the PSP concept. The results of this study indicate that PSP is one of the concepts summarised from several books on fiqh mawarith, specifically a development of the distribution of inheritance carried out in accordance with Sharia law. The determination in the PSP concept concerns the relationship between humans and their Lord, while the distribution concerns the relationship between heirs and other heirs